Increased tumor response to neoadjuvant therapy among rectal cancer patients taking angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers. Issue 16 (20th May 2016) - Morris, Zachary S.; Saha, Sandeep; Magnuson, William J.; Morris, Brett A.; Borkenhagen, Jenna F.; Ching, Alisa; Hirose, Gayle; McMurry, Vanesa; Francis, David M.; Harari, Paul M.; Chappell, Rick; Tsuji, Stuart; et al.
Abstract : BACKGROUND: Angiotensin‐converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are commonly used antihypertensive medications that have been reported to affect aberrant angiogenesis and the dysregulated inflammatory response. Because of such mechanisms, it was hypothesized that these medications might affect the tumor response to neoadjuvant radiation in patients with rectal cancer. METHODS: One hundred fifteen patients who were treated with neoadjuvant radiation at the University of Wisconsin (UW) between 1999 and 2012 were identified. Univariate analyses were performed with anonymized patient data. In a second independent data set, 186 patients with rectal cancer who were treated with neoadjuvant radiation at the Queen's Medical Center of the University of Hawaii (UH) between 1995 and 2010 were identified. These data were independently analyzed as before. Multivariate analyses were performed with aggregate data. RESULTS: Among patients taking ACEIs/ARBs in the UW data set, a significant 3‐fold increase in the rate of pathologic complete response (pCR) to neoadjuvant therapy (52% vs 17%, P = .001) was observed. This finding was confirmed in the UH data set, in which a significant 2‐fold–increased pCR rate (24% vs 12%, P = .03) was observed. Identified patient and treatment characteristics were otherwise balanced between patients taking and not taking ACEIs/ARBs. No significant effect was observed on pCR rates with other medications, including statins, metformin, and aspirin. Multivariate analyses of aggregate data identified ACEI/ARB use as a strong predictor of pCR (odds ratio, 4.02; 95% confidence interval, 2.06‐7.82; P < .001). CONCLUSIONS: The incidental use of ACEIs/ARBs among patients with rectal cancer is associated with a significantly increased rate of pCR after neoadjuvant treatment. Cancer 2016;122:2487–95 . © 2016 American Cancer Society . Abstract : The incidental use of angiotensin‐converting enzyme inhibitors and angiotensin receptor blockers among rectal cancer patients receiving neoadjuvant radiotherapy is associated with an increased rate of pathological complete response. This finding is verified in a second independent database, and a multivariate aggregate analysis shows that the use of these medications is a strong predictor of a pathologic complete response.